Pengaruh Pembiayaan Murabahah, Pembiayaan Musyarakah Dan Non Performing Financing Terhadap Profitabilitas Bank Umum Syariah - Siti Maryam Agustina; Nor Norisanti; Faizal Mulia Z (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
Currently, the economy in Indonesia and even the whole world is experiencing a crisis and paralysis. This is due to the outbreak of the corona virus which is contagious and one of the industries affected is the Islamic banking industry in Indonesia, especially Islamic Commercial Banks (BUS). This study aims to determine the description of murabahah financing, musyarakah financing and non-performing financing on profitability, to determine the magnitude of the effect of murabahah financing, musyarakah financing and non-performing financing on profitability. The method used in this research is descriptive and associative method with a quantitative approach. The sampling technique used using purposive sampling technique is to select samples with certain criteria based on the research objectives. Based on this technique, there are 11 samples of Islamic Commercial Banks (BUS) listed on the Indonesian stock exchange. Data analysis techniques for testing using multiple linear regression analysis. The results showed that murabahah financing had a positive and significant effect on profitability (ROA), musyarakah financing and non-performing financing (NPF) had a negative and significant effect on profitability (ROA) on BUS listed on the Indonesia Stock Exchange for the 2018-2020 period. Keyword : Murabahah, Musharaka, NPF, Profitability